2021
DOI: 10.2147/dmso.s259409
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance, Serum Calcium and Hypertension: A Cross-Sectional Study of a Multiracial Population, and a Similarity Assessment of Results from a Single-Race Population’s Study

Abstract: Background: Recent research suggests the need to assess more ethnic disparities in hypertension (HTN). On the other hand, studies reveal impressive mortality rates due to cardiovascular diseases for some race and ethnic groups compared to others. Methods: We referred to a recent study on serum calcium (SC) and insulin resistance associated with HTN incidence to compare different race groups in the latter found relationship. We compare the current study outcomes with those from the Wu et al study. Results: From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…23 For example, Native American Pima Indians have a high prevalence of obesity but relatively low levels of hypertension. 24 The discovery that the activity of basal muscle SNS in Pima Indians is 20%-30% lower than that of weight-matched white people is one explanation for all of this. 25 This shows that SNS participation is the main factor in hypertension caused by obesity.…”
Section: S N S Over Ac Tivati Onmentioning
confidence: 99%
See 1 more Smart Citation
“…23 For example, Native American Pima Indians have a high prevalence of obesity but relatively low levels of hypertension. 24 The discovery that the activity of basal muscle SNS in Pima Indians is 20%-30% lower than that of weight-matched white people is one explanation for all of this. 25 This shows that SNS participation is the main factor in hypertension caused by obesity.…”
Section: S N S Over Ac Tivati Onmentioning
confidence: 99%
“…It appears to be caused by visceral (rather than subcutaneous) adiposity, race, and sexuality 23 . For example, Native American Pima Indians have a high prevalence of obesity but relatively low levels of hypertension 24 . The discovery that the activity of basal muscle SNS in Pima Indians is 20%–30% lower than that of weight‐matched white people is one explanation for all of this 25 .…”
Section: Sns Overactivationmentioning
confidence: 99%
“…41 A prospective study conducted in Taiwan suggests that higher serum calcium concentrations may precede insulin resistance to promote hypertension, which is consistent with our observations. 40 At present, the following mechanisms related to high calcium concentration and hypertension are considered: 38 (1) the intracellular calcium concentration affects the secretion of catecholamines, angiotensin II, and other hormones; (2) calcium is significantly correlated with an adverse lipid spectrum, such as increased triglyceride concentrations; and (3) serum calcium impairs cholesterol catabolism in the liver, increases lipid synthesis, and plays a role in atherosclerosis.…”
Section: Updating and Re-evaluation Of Model 1 (Model 2)mentioning
confidence: 99%
“…However, variation exists among different ethnics. A study regarding US civilian population showed that Mexican-Americans have lower serum calcium levels than Hispanics, while non-Hispanic blacks have higher serum calcium concentrations than non-Hispanic whites ( 26 ). On the other hand, in disease conditions like chronic kidney disease (CKD), black patients had lower serum calcium concentrations compared with white patients ( 27 ).…”
Section: Introductionmentioning
confidence: 99%